Impact of Storage Temperature on the Expression of Cell Survival Genes in Cultured ARPE-19 Cells. (2nd January 2017) - Pasovic, Lara; Eidet, Jon R.; Olstad, Ole K.; Chen, Dong F.; Lyberg, Torstein; Utheim, Tor P.
ABSTRACT: Purpose : The development of a suitable storage method for retinal pigment epithelium (RPE) is necessary in the establishment of future RPE replacement therapy, and storage temperature has proven to be pivotal for cell survival. ARPE-19, a widely used model for RPE, has been shown to yield the greatest number of viable cells when stored at 16°C compared to other storage temperatures. In this study, we analyze the gene expression profile of cultured ARPE-19 cells after seven days of storage at different temperatures in an effort to predict the gene-level consequences of storage of RPE transplants. Materials and Methods : ARPE-19 cells were cultured until confluence and then stored in minimum essential medium at 4°C, 16°C, and 37°C for seven days. The total RNA was isolated and the gene expression profile was determined using DNA microarrays. The Results were validated using qPCR. Results : Principal component and hierarchical clustering analyses show that the gene expression profiles of cell cultures stored at different temperatures cluster into separate groups. Cultures stored at 4°C cluster closest to the control cultures that were not stored and display the least change in gene expression after storage (157 differentially expressed genes). Cultures stored at 16°C and 37°C display a much larger change in differential gene expression (1787 and 1357 differentially expressed genes, respectively). At 16°C, the expression of several genes with proposed tumor suppressor functions was markedly increased. Changes in regulation of several known signaling pathways and of oxidative stress markers were discovered at both 16°C and 37°C, and activation of the angiogenesis marker vascular endothelial growth factor (VEGF) was discovered at 37°C. There was no evidence of the activation of inflammatory processes in stored cell cultures. Conclusion : ARPE-19 cultures stored at 16°C show the greatest propensity to modulate their gene expression profile in a manner that supports cell survival during storage.